Development of a Nursing Care Model for Patients Undergoing Open-Heart Surgery Using the ASPIRE Framework at Sisaket Hospital - Thanyamai Purinai; Chantira Chiaranai (Journal of SciTech-ASEAN, 2026)
This research and development (R&D) study aimed to develop a nursing care model for patients undergoing open-heart surgery at Sisaket Hospital using the ASPIRE framework (Assess–Set goals–Plan–Implement–Reassess–Evaluate) with multidisciplinary team participation. The study was conducted from August 27, 2025, to January 27, 2026. Participants included 29 nurses, 30 patients, and 11 experts. The research consisted of four phases: (1) situation analysis; (2) development of an integrated care model; (3) tryout and expert evaluation; and (4) outcome evaluation in real-world practice. Data were collected using interview guides, competency assessment forms, satisfaction questionnaires, feasibility assessment forms, and clinical outcome recording forms (CVI = 1.00). Quantitative data were analyzed using the Wilcoxon signed-rank test and paired t-test, whereas qualitative data were analyzed using content analysis. Among providers, nursing staff competency scores increased across all care phases (from 94.92% to 96.98%), and team satisfaction improved with statistical significance (p < 0.001). The feasibility of model implementation was rated at the highest level. Among patients, all seven incidence indicators achieved their specified targets. Indicators achieving 100% included preoperative assessment, intraoperative emergency reporting, and high-alert drug (HAD) management within 1 minute, and rehabilitation/discharge planning. Indicators with zero incidence included surgery cancellation, postoperative arrhythmia, and 7-day readmission. The findings suggest that the SOH-Care nursing care model can reduce surgery cancellations to zero, decrease coagulopathy by 30%, and significantly improve nursing competency. It is recommended that the model be tested in tertiary hospitals with similar contexts and that long-term outcomes be further studied.